2021
DOI: 10.3390/jof7080588
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Invasive Fungal Diseases in Patients with Hematologic Malignancies and Hematopoietic Cell Transplantation Recipients Managed with an Antifungal Diagnostic Driven Approach

Abstract: Patients with hematologic malignancies and hematopoietic cell transplant recipients (HCT) are at high risk for invasive fungal disease (IFD). The practice of antifungal prophylaxis with mold-active azoles has been challenged recently because of drug–drug interactions with novel targeted therapies. This is a retrospective, single-center cohort study of consecutive cases of proven or probable IFD, diagnosed between 2009 and 2019, in adult hematologic patients and HCT recipients managed with fluconazole prophylax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“… 12 The survival rate within 12 weeks was high in our study (73.8%) when compared to previous studies that reported a survival rate of about 60%. 2 , 5 , 21 , 22 Our mortality rate was 26.2% which lower than that reported in prior retrospective cohort studies in Thailand. 5 Our finding suggested that the accessibility of novel antifungal drugs and novel diagnostic tools in recent years may improve the survival outcome of patients.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“… 12 The survival rate within 12 weeks was high in our study (73.8%) when compared to previous studies that reported a survival rate of about 60%. 2 , 5 , 21 , 22 Our mortality rate was 26.2% which lower than that reported in prior retrospective cohort studies in Thailand. 5 Our finding suggested that the accessibility of novel antifungal drugs and novel diagnostic tools in recent years may improve the survival outcome of patients.…”
Section: Discussioncontrasting
confidence: 74%
“…The epidemiology of IFI in patients with HM has also changed recently. Its incidence varies among different regions, ranging 4.6%–15% in Europe, 2 , 15–19 9.6% to 16.2% in South Africa, 20 , 21 and 1.3% to 12% in Asia. 3 , 5 , 22–24 In our study, the incidence of IFI among patients with HM was lower than that reported in the past decade in Thailand (14%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 2, the incidence of invasive fusariosis in patients with hematologic diseases varies across different regions of the globe with the highest incidence reported in Brazil, compared with other countries such as Italy, USA, and Spain [1,12,[28][29][30][31][32][33][34][35].…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…The most frequently identified fungal pathogens are Aspergillus spp. and Candida spp., which significantly contribute to mortality in these patients [ 2 , 3 , 4 , 5 , 6 ]; therefore, mold-active antifungal prophylaxis (MAP) has been established as a standard of care [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, breakthrough IFDs (b-IFDs) in patients receiving antifungal prophylaxis (AFP), including MAP, is an issue for clinicians, alongside with the rising resistance to antifungals and the continuous change in IFD epidemiology, due to both the increased use of mold-active drugs and the improved survival of HM patients.…”
Section: Introductionmentioning
confidence: 99%